G82 Changing the 'no change' culture: increasing usefulness of the SCBU ward round. (25th October 2020) - Marshall, HF; Ajitsaria, R; Taylor, AM; Strauss, CE; Davey, N
Abstract : Aim: This Quality Improvement project aimed to increase the usefulness of ward rounds in a busy Special Care Baby Unit (SCBU; i.e. low dependency neonatal unit). Most babies' primary reasons for remaining inpatient in SCBU are to gain weight and establish oral feeds. Despite this taking weeks for some, they were seen daily on ward round. Baseline data showed that 86% ward round plans for these low risk babies made no changes to management. My aim was to halve this number in four months. Method: Babies that required daily medical review (table 1 ) were identified and excluded from the project, leaving only low risk infants. The medical team were instructed to actively seek out babies of concern by discussion with nurses before ward round. The first PDSA cycle introduced the project to colleagues. Subsequent cycles reduced the frequency of ward round to three times per week, trialling different days. Data was collected from clinical notes. Balancing measures were details of babies that became unwell in the data collection period. Results: The frequency of ward round plans making no changes to management of low risk babies dropped from 86% to 17%, which surpassed the aim. Doctors felt they had more time to help colleagues on the postnatal ward, complete discharge paperwork further in advance (thus facilitating morning discharges) and for projects. Medical and nursing teams were satisfied that well babies were not examined and disturbed daily. Conclusion: Medical and nursing teams are more satisfied with ward rounds occurring three times per week instead of daily for low risk babies in SCBU. More work is needed to look into ways to empower nursing staff to lead on care in low risk babies on their journey to discharge. This project would have had more impact if a reliable measure could be found for staff efficiency.